Appropriate Surveillance Interval after Colonoscopic Polypectomy in Patients Younger than 50 Years - Jung, Yoon Suk (J Korean Med Sci, 2019)
BACKGROUND: Current postpolypectomy surveillance guidelines are based on studies in patients aged ≥50 years. Equal application of the guidelines in patients aged < 50 years may be unreasonable. We aimed to determine an appropriate surveillance interval after adenoma removal in patients aged < 50 years. METHODS: We studied 10,013 patients who underwent ≥ 1 adenoma removal and follow-up colonoscopy. The cumulative risk of metachronous advanced colorectal neoplasia (ACRN) was compared among the eight groups based on age (30–39, 40–44, 45–49 and ≥ 50 years) and baseline adenoma characteristics (low- [LRA] and high-risk adenoma [HRA]). RESULTS: The risk of metachronous ACRN in patients aged 30–39 and 40–44 years with HRA was comparable to that in those aged ≥ 50 years with LRA (P = 0.839 and P = 0.381, respectively). However, the risk in those aged 45–49 years with HRA was higher than in those aged ≥ 50 years with LRA (P = 0.003), and the risk was not significantly different from that in those aged ≥ 50 years with HRA (P = 0.092). Additionally, the 5-year cumulative risk in those aged 45–49 years with LRA was not significantly different from that in those aged ≥ 50 years with LRA. CONCLUSION: The postpolypectomy surveillance interval can be extended up to 5 years in patients aged 30–44 years with HRA, similar to those aged ≥ 50 years with LRA. However, the interval in patients aged 45–49 years with HRA and LRA should be 3 and 5 years, respectively, similar to those aged ≥ 50 years.